Characterization of active compounds from Jatropha gossypifolia L. based on HPTLC - Rofida, Siti; Nailis, Nailis; ., Nurkhasanah; Hayu Nurani, Laela (International Journal of Engineering and Technology, 2019)
Jatropha gossypifolia L. is one of plants that come from Euphorbiaceae family.That is used to be a medicine, particularly as an anticancer. The previous research has reported that the root extract of J.gossypifolia L. (EEAJG) has an ability to kill the cervix cancer cells and breast cancer cells. The cytotoxicity of EEAJG on breast cancer cell lines (T47D) and cervix cancer cell lines (Hella) respectively contained by 43.57 mg/mL and 4.32 mg/mL. The consistency of active compouds on traditional medicine can assurance the biological activity of medicinal plants. Fingerprint profiles of active compouds is either one that can be used to indicate the composition of secondary metabolites in medicinal plants. In this study aims to obtain a fingerprint profiles of active compouds in EEAJG to ensure biological activity as an anticancer based on HPTLC.The root extract of J.gossypifolia L. obtained from extraction by maceration with ethanol. Fingerprint profiles of active compouds can be identified by using High Performance Thin Layer Chromatography (HPLC). Secondary metabolites of EEAJG separated by TLC techniques and scaned wavelength of 254 nm and 366 nm with CAMAG TLC scanner 3. The chromatogram were recorded. The results showed that the chemical compounds were detected at 254 nm produced ten peaks with maximum absorbance at 250-350 nm region. The chemical compounds that were detected at 366 nm produced six peaks with absorbance maximum at 200-350 nm region.Â Â